Measuring method for partial discharges in a high voltage cable system subjected to impulse and superimposed voltage under laboratory conditions. (February 2020) - Wu, Jiayang; Rodrigo Mor, Armando; van Nes, Paul V.M.; Smit, Johan J.
Highlights: A partial discharge (PD) measuring system was investigated and deployed. The measuring system can measure PD in a HV cable joint under impulse conditions. HFCT sensors were used to localize PD and to separate PD from disturbance. Band pass filters enable disturbance suppression and PD detection during impulses. Abstract: A partial discharge (PD) measuring system has been deployed in order to identify and measure PD in a high voltage (HV) cable joint under impulse and superimposed voltages under laboratory conditions. The challenge is to enable the detection of PD during the impulse conditions. The method of measurement has been investigated by introducing an artificial defect in the cable joint in a controlled way to create conditions for partial discharges to occur. Next the HV cable system is subjected to AC, impulse and superimposed voltage. Two high frequency current transformers (HFCT) installed at both ends of the cable joint were used to identify PD from the cable joint and to separate PD from disturbance. Transient voltage suppressors and spark gaps are applied to protect the measuring equipment. Band pass filters with selected characteristics are applied to suppress transient disturbances and increase the chance to detect PD during the impulse. PD signals are separated from transient disturbances during data post processing and by means of pulse polarity analysis. The developed system enables the detection of so-called main and reverse discharges respectively occurring during the rise and tail time of the superimposed impulse. The measurement results obtained show the effectiveness of the presented PD measuring system for investigating the effects of voltage transients on a HV cable system in laboratory conditions.